Media coverage of the unfolding crisis of domestic terrorism in the United States, 1990–2020. (September 2021) - Zulli, Diana; Coe, Kevin; Isaacs, Zachary; Summers, Ian
Public relations research has paid considerable attention to foreign terrorist crises but relatively little attention to domestic ones—despite the growing salience of domestic terrorism in the United States. This study content analyzes 30 years of network television news coverage of domestic terrorism to gain insight into four theoretical issues of enduring interest within the literature on news framing and crisis management: sourcing, contextualization, ideological labeling, and definitional uncertainty. Results indicate that the sources called upon to contextualize domestic terrorism have shifted over time, that ideological labels are more often applied on the right than the left, and that definitional uncertainty has increased markedly in recent years. Implications for the theory and practice of public relations and crisis management are discussed.